Show me the numbers: a quantitative portrait of the attitudes, experiences, and values of philosophers of science regarding broadly engaged work - Kathryn S. Plaisance; Alexander V. Graham; John McLevey; Jay Michaud (Synthese, 2019)
Philosophers of science are increasingly arguing for the importance of doing scientifically- and socially-engaged work, suggesting that we need to reduce barriers to extra-disciplinary engagement and broaden our impact. Yet, we currently lack empirical data to inform these discussions, leaving a number of important questions unanswered. How common is it for philosophers of science to engage other communities, and in what ways are they engaging? What barriers are most prevalent when it comes to broadly disseminating one’s work or collaborating with others? To what extent do philosophers of science actually value an engaged approach? Our project addresses this gap in our collective knowledge by providing empirical data regarding the state of philosophy of science today. We report the results of a survey of 299 philosophers of science about their attitudes towards and experiences with engaging those outside the discipline. Our data suggest that a significant majority of philosophers of science think it is important for non-philosophers to read and make use of their work; most are engaging with communities outside the discipline; and many think philosophy of science, as a discipline, has an obligation to ensure it has a broader impact. Interestingly, however, many of these same philosophers believe engaged work is generally undervalued in the discipline. We think these findings call for cautious optimism on the part of those who value engaged work—while there seems to be more interest in engaging other communities than many assume, significant barriers still remain.